Delayed Massive Hydrothorax Following Subclavian Catheter Insertion: An Unusual Complication. Issue 4 (October 2015) - Aggarwal, Richa; Soni, Kapil Dev
Abstract : Complications of central venous catheter can become life threatening if not managed timely. We present a case of massive hydrothorax that developed few hours after placement of the central venous pressure line. The diagnosis was little delayed because the catheter was normally placed initially and later got displaced within few hours of shifting to the intensive care unit. However, the patient was managed timely. Our case report suggests that the position of the catheter should be checked frequently in the intensive care unit and particularly so after shifting and positioning of the patient and the associated complications should be kept in mind.